Inactivating mutations and hypermethylation of the NKX2‐1/TTF‐1 gene in non‐terminal respiratory unit‐type lung adenocarcinomas. Issue 9 (29th July 2017) - Matsubara, Daisuke; Soda, Manabu; Yoshimoto, Taichiro; Amano, Yusuke; Sakuma, Yuji; Yamato, Azusa; Ueno, Toshihide; Kojima, Shinya; Shibano, Tomoki; Hosono, Yasuyuki; Kawazu, Masahito; Yamashita, Yoshihiro; et al.
Abstract : The major driver mutations of lung cancer, EGFR mutations and EML4‐ALK fusion, are mainly detected in terminal respiratory unit (TRU)‐type lung adenocarcinomas, which typically show lepidic and/or papillary patterns, but are rarely associated with a solid or invasive mucinous morphology. In order to elucidate the key genetic events in non‐TRU‐type lung cancer, we carried out whole‐exome sequencing on 43 non‐TRU‐type lung adenocarcinomas based on morphology (17 acinar, nine solid, and two enteric adenocarcinomas, and 15 adenocarcinomas with a mucinous morphology). Our analysis identified mutations in TP53 (16/43, 37.2%), KRAS (13/43, 30.2%), and NKX2‐1/TTF‐1 (7/43; 16.3%) as the top three significantly mutated genes, while the EGFR mutation was rare (1/43, 2.3%) in this cohort. Eight NKX2‐1/TTF‐1 mutations (five frameshift, two nonsense, and one missense) were identified, with one case harboring two distinct NKX2‐1/TTF‐1 mutations (one missense and one frameshift). Functional assays with the NK2 homeobox 1 (NKX2‐1)/thyroid transcription factor 1 (TTF‐1) mutants revealed that none of them retain the activity as a transcriptional factor. Histologically, invasive mucinous adenocarcinomas accounted for most of the NKX2‐1/TTF‐1 mutations (five cases), as well as one enteric and one acinar adenocarcinoma. Immunohistochemistry showed that the cohort was largely divided into TTF‐1‐postive/hepatocyte nuclear factor 4‐α (HNF4‐α)‐negative and TTF‐1‐negative/HNF4‐α‐positive groups. NKX2‐1/TTF‐1 mutations were exclusively found in the latter, in which the gastrointestinal markers, mucin 5AC and cytokeratin 20, were frequently expressed. Bisulfite sequencing revealed that the NKX2‐1/TTF‐1 gene body was highly methylated in NKX2‐1/TTF‐1‐negative cases, including those without the NKX2‐1/TTF‐1 mutations. The genetic or epigenetic inactivation of NKX2‐1/TTF‐1 may play an essential role in the development and aberrant differentiation of non‐TRU‐type lung adenocarcinomas. Abstract : Our histological and immunohistochemical analysis in this cohort showed that HNF4‐alpha was not specific for mucinous adenocarcinomas but was widely expressed in non‐TRU‐type adenocarcinomas. Furthermore, we revealed that NKX2‐1 mutated cancers showed various histological subtypes: acinar, enteric, and mucinous adenocarcinomas, and that all of the NKX2‐1 mutated cancers were positive for HNF4‐alpha and negative for TTF‐1 in common. We also performed bisulfite sequencing and revealed that NKX2‐1/TTF‐1 genes were highly methylated in TTF‐1 negative cases, including those without NKX2‐1 mutations.